Does rewarding pedagogical excellence keep teachers in the classroom? Evidence from a voluntary award program - Samuel G. Berlinski; Alejandra Ramos (Inter-American Development Bank (IDB), 2018)
We analyze the effects on teacher retention and between school mobility of a program that rewards excellence in pedagogical practice in Chile. Teachers apply voluntarily for the award and those who succeed on a set of assessments receive a 6 percent annual wage increase for up to 10 years. We use a sharp regression discontinuity design to identify the causal effect of receiving the award. Using administrative data over several cohorts of applicants, our estimates indicate that locally the award does not alter transitions out of the school system. This suggests that around the threshold the skills rewarded by the program are not strongly correlated with the value of the teachers' outside option. We observe, however, an increase in mobility within the school system among teachers that receive the award. These mobility patterns are consistent with the award providing a signal of teacher ability.
Keywords: I21; J45; J63; M52; 330; Employee turnover rates; Public sector compensation; Teachers